2013
DOI: 10.1021/am3023898
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dot-Based Field-Effect Transistors and Their Ligand Length-Dependent Carrier Mobility

Abstract: We report electrical measurements of films of carbon quantum dots (CQDs) that serve as the channels of field-effects transistors (FETs). To investigate the dependence of the field-effect mobility on ligand length, colloidal CQDs are synthesized and ligand-exchanged with several primary amines of different ligand lengths. We measure current as a function of gate voltage and find that the devices show ambipolar conductivity, with electron and hole mobilities as high as 8.49 × 10(-5) and 3.88 × 10(-5) cm(2) V(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 40 publications
(84 reference statements)
4
27
0
1
Order By: Relevance
“…The physical reason behind such high‐speed response in our photodiode is not only due to the energy alignment in our device as we have discussed above, but also due to appropriate selection of QD surface termination ligands . When we compare our device's optical response with QDs that have MPA and OA terminations, respectively, we can see that the optical response speed is twofold slower in OA‐terminated QDs (Figure S4, Supporting Information), with rising and falling times calculated as 77.6 ± 8.54 and 100 ± 14.70 ns, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…The physical reason behind such high‐speed response in our photodiode is not only due to the energy alignment in our device as we have discussed above, but also due to appropriate selection of QD surface termination ligands . When we compare our device's optical response with QDs that have MPA and OA terminations, respectively, we can see that the optical response speed is twofold slower in OA‐terminated QDs (Figure S4, Supporting Information), with rising and falling times calculated as 77.6 ± 8.54 and 100 ± 14.70 ns, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…Except for above discussed devices, CDs or GQDs with appropriate band gap and conductivity can compensate for the disadvantages of graphene to fabricate field effect transistors (FETs). Actually, FETs have been studied by Kwon et al via solution method, effects of doping and ligand length on the performance of FETs are studied . We are expecting more researches about FETs based on CDs and GQDs for electrochemical and biological sensing.…”
Section: Discussionmentioning
confidence: 99%
“…We have also studied electronic properties of CQDs and found that trap states caused by surface defects of CQDs take part in electronic conduction . Several reports have shown the prospective electrical behavior of carbon quantum dots but still more studies are required for an adequate understanding of its’ electronic nature …”
Section: Introductionmentioning
confidence: 99%